Experimental validation of an analytical microdosimetric model based on Geant4-DNA simulations by using a silicon-based microdosimeter. (November 2020) - Bertolet, A.; Grilj, V.; Guardiola, C.; Harken, A.D.; Cortés-Giraldo, M.A.; Baratto-Roldán, A.; Fleta, C.; Lozano, M.; Carabe, A.
Abstract: Purpose: To study the agreement between proton microdosimetric distributions measured with a silicon-based cylindrical microdosimeter and a previously published analytical microdosimetric model based on Geant4-DNA in-water Monte Carlo simulations for low energy proton beams. Methods and material: Distributions for lineal energy ( y ) are measured for four proton monoenergetic beams with nominal energies from 2.0 MeV to 4.5 MeV, with a tissue equivalent proportional counter (TEPC) and a silicon-based microdosimeter. The actual energy for protons traversing the silicon-based microdosimeter is simulated with SRIM. Monoenergetic beams with these energies are simulated with Geant4-DNA code by simulating a water cylinder site of dimensions equal to those of the microdosimeter. The microdosimeter response is calibrated by using the distribution peaks obtained from the TEPC. Analytical calculations for y ‾ F and y ‾ D using our methodology based on spherical sites are also performed choosing the equivalent sphere to be checked against experimental results. Results: Distributions for y at silicon are converted into tissue equivalent and compared to the Geant4-DNA simulated, yielding maximum deviations of 1.03% for y ‾ F and 1.17% for y ‾ D . Our analytical method generates maximum deviations of 1.29% and 3.33%, respectively, with respect to experimental results. Conclusion: Simulations in Geant4-DNA with ideal cylindrical sites in liquid water produce similar results to the measurements in an actual silicon-based cylindrical microdosimeter properly calibrated. The found agreement suggests the possibility to experimentally verify the calculated clinical y ‾ D with our analytical method. Highlights: Validation of analytical microdosimetric models for protons of low energy. Silicon-based microdosimeter is calibrated and employed for experimental data. Distributions and averages of lineal energy are compared. We found agreement among experiments, Geant4-DNA and analytical results.